Folate Administration Increases n-3 Polyunsaturated Fatty Acids in Rat Plasma and Tissue Lipids - Pita, María-Luisa; Delgado, María-José (Thrombosis and Haemostasis, 2000)
It has been shown that folic acid deficiency can modify polyunsaturated fatty acid (PUFA) metabolism and thus could contribute to the development of cardiovascular diseases. We have studied the effect of folate administration on fatty acid composition of plasma, platelet, erythrocyte, intestinal and liver lipids. Two groups of rats were daily injected with either saline solution (control group) or 5-methyl-tetrahydrofolate (MTHF) solution (MTHF group) for 15 days. Changes induced by folate treatment on n-6 PUFA were not very significant. Linoleic acid only decreased in liver and intestinal phospholipids of MTHF rats whereas arachidonic acid was unaffected by folate administration. However, n-3 PUFA significantly increased in plasma lipid fractions and in platelet, erythrocyte and intestinal phospholipids. It is well known that n-3 PUFA show antithrombotic properties. Thus, the increase of n-3 PUFA observed after MTHF administration might contribute to the prevention of vascular disorders.
Keywords: Folate; n-3 fatty acids